Methodological Backgrounds of the English Language Professionally Oriented Listening Competence Formation of Economic Specialty Students - Nadiya Hupka-Makohin (Pedagogical Discourse, 2020)
The content of English professionally oriented competence in listening of the students of economic specialties has been theoretically analyzed and scientifically substantiated in the article. The regularities of the structure and component composition of educational process in a non-linguistic higher education institution have been established.The typology of competences for future specialists in economics and the main methodological approaches to the formation of English language professionally oriented listening in a non-linguistic higher educational institution have been characterized to develop new methods of self-study English professionally oriented listening of the future economists for enhancing their competitiveness at the labour market.At the present stage of the society development, the ultimate goal of learning a foreign language in the non-linguistic higher educational institution is to develop the personality of economic specialties students to be mobile and capable of self-education, self-realization and participation in foreign language intercultural communication. The implementation of the educational process can be complete only if the professional component is taken into account. Therefore, we see the prospects for further research considering the components of the content of English vocational listening in a non-linguistic higher educational institution to develop a methodology for forming English vocational listening of the future economists that will promote the mobility of bachelors and their competitiveness.The results of the training control of English-speaking professionally oriented listening of the future economists have been presented, on the basis of English-speaking professionally oriented listening requirements  in accordance with the types of listening have been singled out, such as: understanding of the main content of the audio text, which involves first of all the understanding of the future employee of the economics of the topic and the most important details of the audio text; listening to find the necessary information or information of interest involves the student's understanding of specific information; listening with a full understanding of the audio text involves the student's understanding of the most complete and accurate information. A comparative analysis of professionally oriented listening skills, which are part of the communicative and professional competence of students of economic specialties, has been carried out.